THE RELATIONSHIP BETWEEN THE DURATION OF HYPERTENSION AND ANXIETY AMONG HYPERTENSIVE PATIENTS IN THE SERVICE AREA OF THE LEMBO COMMUNITY HEALTH CENTER NORTH KONAWE REGENCY - Indra; Nurnianingsih A. Yasin; Sri Yulian Hunowu; Moh. Nisyar Sy. Abd. Azis; Sartika; Bergita Dumar (JTH: Journal of Technology and Health, 2026)
Hypertension is a chronic condition that is common among adults and is often associated with various psychological issues, including anxiety levels. As a chronic condition, the longer a person has hypertension, the higher their anxiety levels tend to be. This condition can affect patients’ psychological well-being, adherence to treatment, and quality of life if not managed properly. Given these circumstances, this study aims to examine the association between the duration of hypertension and anxiety levels among adult patients at the Lembo Community Health Center. This is a quantitative study using a cross-sectional study design. The study involved 59 respondents selected through cluster sampling. Data were collected using the Zung Anxiety Scale to assess anxiety levels and were analyzed using the chi-square test. The findings showed a significant relationship between the duration of hypertension and anxiety levels, with a p-value of 0.000 (p < 0.05). These findings suggest that a longer duration of hypertension may contribute to a higher risk of anxiety among adult patients. The results of this study underscore the importance of long-term management of chronic diseases, particularly hypertension, as a means to reduce the risk of anxiety in adult patients and to support the provision of more comprehensive healthcare services that address both physical and psychological aspects.